Chromosome 2p gain in monoclonal B‐cell lymphocytosis and in early stage chronic lymphocytic leukemia12. Issue 1 (9th October 2012) - Fabris, Sonia; Mosca, Laura; Cutrona, Giovanna; Lionetti, Marta; Agnelli, Luca; Ciceri, Gabriella; Barbieri, Marzia; Maura, Francesco; Matis, Serena; Colombo, Monica; Gentile, Massimo; Recchia, Anna Grazia; et al.
Abstract Recent studies have described chromosome 2p gain as a recurrent lesion in chronic lymphocytic leukemia (CLL). We investigated the 2p gain and its relationship with common prognostic biomarkers in a prospective series of 69 clinical monoclonal B‐cell lymphocytosis (cMBL) and 218 early stage (Binet A) CLL patients. The 2p gain was detected by FISH in 17 patients (6%, 16 CLL, and 1 cMBL) and further characterized by single nucleotide polymorphism‐array. Overall, unfavorable cytogenetic deletions, i.e., del(11)(q23) and del(17)(p13) (P = 0.002), were significantly more frequent in 2p gain cases, as well as unmutated status of IGHV (P < 1 × 10−4) and CD38 (P < 1 × 10−4) and ZAP‐70 positive expression (P = 0.003). Furthermore, 2p gain patients had significantly higher utilization of stereotyped B‐cell receptors compared with 2p negative patients (P = 0.009), and the incidence of stereotyped subset #1 in 2p gain patients was significantly higher than that found in the remaining CLLs (P = 0.031). Transcriptional profiling analysis identified several genes significantly upregulated in 2p gain CLLs, most of which mapped to 2p. Among these, NCOA1 and ROCK2 are known for their involvement in tumor progression in several human cancers, whereas among those located in different chromosomes, CAV1 at 7q31.1 has been recently identified to play a critical role in CLL progression. Thus, 2p gain can be present since the early stages of the disease, particularly in those cases characterized by other poor prognosis markers. The finding of genes upregulated in the cells with 2p gain provides new insights to define the pathogenic role of this lesion. Am. J. Hematol. 2013. © 2012 Wiley Periodicals, Inc.